Orbital Cellulitis and Endophthalmitis Associated with Odontogenic Paranasal Sinusitis. - Riyanto, Heny (Airlangga University Press, 2009)
The objective of this study is to report a case and management of orbital cellulitis complicated with endophthalmitis caused by paranasal sinusitis associated with dental infection. A case report, a 44-year-old man presented at outpatient clinic with painful and inflamed proptosis on the right eye in 4 days, visual loss. His upper right cheek was swelling and had a history of dental carries on his maxillary teeth a week ago. On examination the visual acuity was no light perception, conjuntival hyperemia, chemosis, corneal thinning, and total hypopion. Right fixed ocular motility and periorbital inflamation were found. Computed Tomograph (CT) scan examination revealed deformity of the right orbit caused by lession in the orbital apex with intraconal extension along the medial orbital wall into the maxillary and ethmoidal sinus with gasforming appearance. Periorbital abcess was incised and drained, intravenous broad spectrum antibiotic was administered. The patient was consulted to Otolaryngology Department and Dentistry Department. Surgery of the ocular and paranasal sinus were planned under general anesthesia. Enucleation and debridement of periorbital abcess were performed. Caldwell-Luc technique was performed by the otolaryngologist to evacuate purulent material in the paranasal sinuses. On the follow up showed good result and the ocular prosthesis was planned. Orbital cellulitis complicated with endophthalmitis caused by paranasal sinusitis related with dental infection need special attention. Adequate treatment and multidisciplinary management are needed to prevent more severe complications.